2020
DOI: 10.1002/hed.26402
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of head and neck squamous cell carcinoma after bone marrow transplant

Abstract: The risk of developing head and neck squamous cell carcinoma (HNSCC) in patients with graft versus host disease (GVHD) after bone marrow transplant (BMT) is well established but large series reporting outcomes are sparse. Methods: Retrospective, single institution, study of patients with GVHD and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…GVHD is a reaction of the immune system that occurs when cells from an immunocompetent patient are transplanted into an immunodeficient patient. The risk of developing malignancies secondary to HSCT is multifactorial and after transplantation the incidence of secondary malignancies increases over time ( 1 , 6 , 31 - 33 ). In this sense, the objective of this paper is to present a study on OSCC developed in areas of oral mucosa that had GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…GVHD is a reaction of the immune system that occurs when cells from an immunocompetent patient are transplanted into an immunodeficient patient. The risk of developing malignancies secondary to HSCT is multifactorial and after transplantation the incidence of secondary malignancies increases over time ( 1 , 6 , 31 - 33 ). In this sense, the objective of this paper is to present a study on OSCC developed in areas of oral mucosa that had GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo HSCT have been reported to develop tumors at a younger age and higher rate 7,16 . Acute and chronic graft versus host disease after transplant have been associated with increased rates of head and neck malignancy in non‐FA patients and may provide an explanation for why FA patients are at greater risk after transplant 7,17 . Bone marrow radiation and cyclophosphamide are also independent risk factors for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Acute and chronic graft versus host disease after transplant have been associated with increased rates of head and neck malignancy in non-FA patients and may provide an explanation for why FA patients are at greater risk after transplant. 7,17 Bone marrow radiation and cyclophosphamide are also independent risk factors for malignancy. All patients who developed head and neck cancer in our study had undergone HSCT, but our population of un-transplanted patients is too small, (10%), to make a useful comparison.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that in solid-organ transplanted patients there is a 20 times higher risk of developing secondary malignancy, compared to the general population, mainly due to higher dose of immunosuppressive therapies [ 40 , 41 ]. Douglas et al showed that the most affected site of squamous cell cancer in the head and neck after HSCT was the oral cavity, in particular the tongue, and they showed that cancer in these patients had a more aggressive progression and a poorer prognosis [ 42 ]. In our patient sample, all of the patients were treated with a conditioning chemotherapy regimen, and, among them, three patients also underwent radiotherapy.…”
Section: Discussionmentioning
confidence: 99%